Where winter finds you : a Caldwell Christmas - Ward, J. R., 1969- (Ward, J. R., 1969- Black dagger brotherhood series., 2019)
"#1 New York Times bestselling author J.R. Ward is heating things up this winter with a holiday novel featuring some of her most iconic Black Dagger Brothers"--